Mannose-Decorated Dendritic Polyglycerol Nanocarriers Drive Antiparasitic Drugs To Leishmania infantum-Infected Macrophages - Laura I. Vossen; Bárbara Domínguez-Asenjo; Camino Gutiérrez-Corbo; M. Yolanda Pérez-Pertejo; Rafael Balaña-Fouce; Rosa María Reguera; Marcelo Calderón (Pharmaceutics, 2020)
Macrophages are hosts for intracellular pathogens involved in numerous diseases including leishmaniasis. They express surface receptors that may be exploited for specific drug-targeting. Recently, we developed a PEGylated dendritic polyglycerol-based conjugate (PG–PEG) that colocalizes with intracellular parasite. We hereby study the effect of surface decoration with mannose units on the conjugates’ targeting ability toward leishmania intracellular parasites. Murine and human macrophages were exposed to fluorescently labeled mannosylated PG–PEG and uptake was quantified by flow cytometry analysis. Nanocarriers bearing five mannose units showed the highest uptake, which varied between 30 and 88% in the population in human and murine macrophages, respectively. The uptake was found to be dependent on phagocytosis and pinocytosis (80%), as well as clathrin-mediated endocytosis (79%). Confocal microscopy showed that mannosylated PG–PEGs target acidic compartments in macrophages. In addition, when both murine and human macrophages were infected and treated, colocalization between parasites and mannosylated nanoconjugates was observed. Leishmania-infected bone marrow-derived macrophages (BMM) showed avidity by mannosylated PG–PEG whereas non-infected macrophages rarely accumulated conjugates. Moreover, the antileishmanial activity of Amphotericin B was kept upon conjugation to mannosylated PG–PEG through a pH-labile linker. This study demonstrates that leishmania infected macrophages are selectively targeted by mannosylated PEGylated dendritic conjugates.